Case-control study examining the association between hip fracture risk and statins therapy in old people - Cheng, Kao-Chi; Liao, Kuan-Fu; Lin, Cheng-Li; Lin, Cheng-Chieh; Lai, Shih-Wei (Medicine (Baltimore), 2019)
A population-based case-control study investigated possible association between statin use and risk of hip fracture among the elderly in Taiwan.The Taiwan National Health Insurance Program database was used to identify 7464 subjects aged 65 years or older with newly diagnosed hip fracture in 2000 to 2013. An additional 7464 subjects aged 65 years or older without hip fracture were randomly selected as the control group. Hip fracture cases and controls were matched for sex, age, comorbidities, and index year of hip fracture diagnosis. Statin use was defined as "current," "recent," or "past" if the patient's statin prescription was respectively filled <3, 3 to 6, or ≥6 months before the date of the hip fracture. The odds ratio (OR) and 95% confidence interval (CI) for hip fracture associated with statin use was estimated using the logistic regression model.The logistic regression analysis demonstrated that the odds of current statin use in cases with hip fracture were lower than the odds of current statin use in subjects without hip fracture (adjusted OR 0.73, 95% CI 0.65, 0.82).The odds of current statin use in cases with hip fracture were lower than the odds of current statin use in subjects without hip fracture in elderly people in Taiwan.